Manual de calidad para certificación de acuerdo a la norma NTC ISO9001:2000 para la empresa Interventorías y Consultorías del Caribe S.A. (2005)
In this work we are presenting the manual of quality corresponding to the company interventorías and consultancies of the Carib s.a. based on the norm ntc iso 9001:2000, in order to that the company takes the decision to be certified. This manual describes the system of quality management adopted as the company of interventoría and consultancy. That fulfills with the requisites of the norm ISO 9001:2000 The quality manual serves like letter of credence of our company and projects our image before the market. In him there is described the whole process of the system of management of the quality, according to our politics and targets of. Also, this document serves to us as support for the programs of training of the personnel that deposits the empresaresistencia to the compression of this one concrete